The Legal Substance Ownership of Motor Vehicle Owner's Book - Etna Yesinia Mardianti; Maryanto Maryanto (Law Development Journal, 2021)
The purpose of this research is to analyze the legal substance concerning the Motor Vehicle Ownership Book in terms of current positive legal aspects. The research method in this article is normative juridical. The results showed that the normative law of ownership of proof of ownership of motor vehicles has legal force as a means of protecting society and providing legal certainty. The strategic role of the BPKB as a valid means of evidence and its legitimacy is recognized by the State, in addition to that as a means of uncovering crimes related to motorized vehicles, both as objects (targets) of crime and as predicate of crimes (means or means). BPKB's juridical ownership scheme, rooted in the Preamble of 1945 Constitution of the Republic of Indonesia up to laws and regulations such as Act No. 22 of 2009 concerning Road Traffic and Transportation as well as Regulation of the Chief of Police Number 5 of 2012 concerning Registration and Identification of Motor Vehicles.